Web-Based Geographic Information System Model for Construction Business Surveys - Siti Fathimah; Syarifullah Abdi; Wahyudi Ariannor (Progresif: Jurnal Ilmiah Komputer, 2025)
The construction business survey conducted by BPS Banjarbaru City frequently encounters challenges such as unclear business addresses, including the absence of house numbers or RT/RW, and annual changes of survey personnel, resulting in inconsistencies in data collection. This study aims to develop a web-based Geographic Information System (GIS) to address these issues. The Rapid Application Development (RAD) method was employed to ensure the system meets user requirements. Functional testing results demonstrate that all features evaluated operate as intended, ensuring the system supports survey efficiency, addresses issues with unclear addresses, and maintains data continuity across survey periods. Thus, the system provides an effective solution to the challenges faced in construction business surveys conducted by BPS Banjarbaru City.Keywords: Geographic Information System; Business entity survey; Construction AbstrakSurvei badan usaha konstruksi yang dilakukan oleh BPS Kota Banjarbaru sering menghadapi kendala berupa alamat badan usaha yang kurang jelas, seperti tidak tercantumnya nomor rumah atau RT/RW, serta pergantian petugas survei setiap tahun yang menyebabkan ketidakkonsistenan dalam pendataan. Penelitian ini bertujuan untuk mengembangkan Sistem Informasi Geografis (SIG) berbasis web sebagai solusi untuk mengatasi permasalahan tersebut. Metode Rapid Application Development (RAD) diterapkan untuk memastikan sistem sesuai dengan kebutuhan pengguna. Hasil pengujian fungsionalitas sistem menunjukkan bahwa, seluruh fitur yang diuji berfungsi sesuai dengan kebutuhan pengguna, memastikan sistem dapat mendukung efisiensi survei, mengatasi kendala alamat tidak jelas dan menjaga kesinambungan data antarperiode survei. Dengan demikian, sistem ini memberikan solusi permasalahan dalam survei badan usaha konstruksi di BPS Kota Banjarbaru.Kata kunci: Sistem Informasi Geografis; Survei badan usaha; Konstruksi